Annual crop yield variation, child survival and nutrition among subsistence farmers in Burkina Faso - Belesova, Kristine; Sauerborn, Rainer (American journal of epidemiology, 2017)
Whether year to year variation in crop yields affects the nutrition, health, and survival of subsistence farming populations is relevant to the understanding of the potential impacts of climate change. However, the empirical evidence is limited. We examined the association of child survival with inter-annual variation in food crop yield and middle-upper arm circumference (MUAC) in a subsistence farming population of rural Burkina Faso. The study was of 44,616 children < 5 years of age included in the Nouna Health and Demographic Surveillance System, 1992-2012, whose survival was analysed in relation to the food crop yield in the year of birth (which ranged from 65% to 120% of the period average) and, for a subset of 16,698 children, to MUAC, using shared frailty Cox proportional hazards models. Survival was appreciably worse in children born in years with low yield (fully adjusted hazard ratio of 1.11 (95% confidence interval: 1.02, 1.20) for a 90th to 10th centile decrease in annual crop yield) and in children with small MUAC (hazard ratio 2.72 (95% confidence interval: 2.15, 3.44) for a 90th to 10th centile decrease in MUAC). These results suggest an adverse impact of variations in crop yields which could increase under climate change.